MAKNA TARI TORTOR DALAM UPACARA ADAT PERKAWINAN SUKU BATAK TOBA DESA TANGGA BATU KECAMATAN TAMPAHAN KABUPATEN TOBA SAMOSIR PROVINSI SUMATERA UTARA - Tati Diana; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Batak Toba is a tribe that has a traditional dance. Batak Toba traditional dance called tortor. Tortor is a dance that animates the whole body with the required rhythm gondang the center of the movement of the hands and fingers, feet and legs, back and shoulders. While the dancers tortor (dance) is called with panortor. Motion in tortor (dance) is important. Motion in tortor (dance) adjusted to the position panortor (dancer) in the concept of kinship Dalihan Na Tolu. Tortor (dance) has an important role in every event Batak, but can be clearly aware that there are many Toba Batak people who do not understand the meaning of each movement tortor dance during the wedding ceremony in the village of Tangga Batu. Analysis of the data used to answer the problems that exist in this research is qualitative descriptive approach were further analyzed based on the theories in this research is purposive sampling where the number of informants of 5 people consisting of one traditional leaders and the 4 participants vote who witnessed tortor. From the results of research in the field that tortor in marriage ceremonies show that every hand movement has a meaning and significance of each activity tortor. Hand movements have meaning, namely: Maneanea means asking for blessings, mamasu-masu means to give thanks, old mangido means to ask and receive blessings and manomba respecting the parents of his wife. The results of this research shows that the majority of Batak Toba people do not know what is contained in tortor dance in Toba Batak wedding ceremony. The wedding ceremony in the village of Batu Tangga not use musical accompaniment in the form of gondang, but replaced with a musical accompaniment keyboard music, because it is more practical and modren. Shifting now to own women's fashion wear kebaya and Ulos wrapped around the outside of clothing. Based on the results of the study are already many people who become panortor on custom events marriage leave culture to wear Ulos as one tool in manortor that should be used, and not infrequently encountered many of the panortor or female dancers did not wear gloves or wearing only pants only when will participate manortor thus reducing the value of modesty.Keywords: Meaning, Dancing, Wedding